Penguatan Kapasitas KKG PAUD melalui Pelatihan Berjenjang dan Mentoring Instruktur Lokal Berbasis Media Berkelanjutan di Gugus V Loa Janan - Cisyulia Octavia; Andi Farid Hidayanto; Dian Dwi Nur Rahmah (Jurnal Surya Masyarakat, 2026)
The sustainability of early childhood teacher empowerment programs is often hindered by dependence on external facilitators. Building on the success of the first training phase, which developed educational media using local materials at TK Bina Anaprasa Melati, the second phase of this community service program was designed to ensure the dissemination and continuity of innovation through a Tiered Training and Local Instructor Mentoring model. This empowerment initiative employed a Participatory Action Research (PAR) approach, a participatory method that links reflection and action for community empowerment, by applying the Gradual Release of Responsibility (GRR) framework. GRR gradually shifted the facilitator’s role from the external team to two selected local instructor candidates. The program involved 21 new early childhood teachers from Cluster V Loa Janan and was conducted at TK A’Sidiq. Data were collected through participatory observation, 360° feedback questionnaires (comprehensive multi-source performance evaluation), interviews, and document analysis. Results indicated a significant improvement in the pedagogical competence of instructor candidates (teaching ability scores increased from 3.2 to 4.5). Training participants expressed highly positive responses (satisfaction score of 4.7/5), and 95% successfully created 3D murals and creative fence dolls. The establishment of an internal replication mechanism, including follow-up training action plans and a sustainable learning media working group, served as a strong indicator of program sustainability. This model proved effective in building community capacity and fostering independence in educational innovation rooted in local wisdom.